PEMANFAATAN LENGKUAS (Alpinia galanga) DALAM MENGAWETKAN BAKSO - Budi Hardiansyah Siregar; Wirsal Hasan; Surya Dharma (Lingkungan dan Kesehatan Kerja, 2014)
Applying Galangal (Alpinia galanga) in Preserving The Meatballs. Meatballs are one of Indonesian favorite foods who have short preserving time. Handling these problems, the meatball producers and traders using harmful preservatives which have bad effects on people’s health who love to eat meatballs. The research’s purpose was to determine the ability of galangal (Alpinia galanga) in extending the meatballs preserving time. The research type was Quasy Experiment with a completely randomized design. Meatball samples were treated by adding galangal to its boiling process with concentration of 100 grams, 200 grams, 300 grams on each 250 grams meatball’s dough and 0 gram as a control in 3 l water. Each treatment performed 5 repetitions. The result showed an average meatballs preserving time at concentration of galangal 0 gram (control) is 19 hours 12 minutes, at concentration of 100 grams is 26 hours 24 minutes, at concentration of 200 grams is 24 hours 48 minutes, at concentration of 300 grams is 22 hours 24 minutes. Based on dependent t results showed a significant difference between treatments with range of galangal concentrations in extending the meatballs preserving time. The LSD test results showed that the concentration of galangal who can have the longest meatballs preserving time is at concentration of 100 grams galangal Thus, producers and traders can use galangal as meatballs preservative which are safe for health. Addition of ginger should be done when meatballs boiling water is not in boiling condition (± 50-60 oC) and it is suggested to use young galangal. Keywords : Meatballs, Galangal, Meatball Preserving Time